Small states and international security Europe and beyond - Archer, Clive; Bailes, Alyson J. K.; Wivel, Anders (New York : Routledge, 2014)
'The book explains what'small' states are and explores their current security challenges, in general terms and through specific examples. It reflects the shift from traditional security definitions emphasising defence and armaments, to new security concerns such as economic, societal and environmental security where institutional cooperation looms larger. These complex issues, linked with traditional power relations and new types of actors, need to be tackled with regard to democracy and good governance. Key policy challenges for small states are examined and applied in the regional case studies.The book deals mainly with the current and recent past of such states but also offers insights for their future policies. Although many of the states covered are European, the study also includes African, Caribbean and Asian small states. Their particular interest and relevance is outlined, as is the connection between their security challenges and their smallness. Policy advice for other states is then sought. The book is the first in-depth, multi-continent study of security as an aspect of small state governance today. It is novel in placing the security dilemmas of small states in the context of wider ideas on international and institutional change, and in dealing with non-European states and areas'-- Provided by publisher.
'This book offers an accessible, coherent and informative analysis of contemporary and future security challenges facing small states and provides a comparative perspective'-- Provided by publisher.
pt. 1. Small state security revisited : history, concepts, theory -- pt. 2. Small state security in Europe -- pt. 3. Comparative insights.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: States, Small; States, Small -- Foreign relations; Security, International -- Case studies; States, Small -- Economic conditions; States, Small -- Case studies; National security; States, Small -- Europe; Electronic books